Differences in production decline characteristics of horizontal wells in tight gas sandstone reservoirs with different qualities: A case study of the Sulige gas field, Ordos Basin - Cheng, Minhua; Wei, Yunsheng; Ji, Guang; Ning, Bo; Zhao, Meng (Frontiers in Energy Research, 2023)
Horizontal well development is one of the important means to improve the well production of tight gas reservoir and realize the effective development of tight gas. Based on abundant static and dynamic data of a large number of horizontal wells that have been put into operation, carry out structure characteristics of tight reservoir, detail geologic analysis of effective reservoir drilled by horizontal well and development dynamic analysis，three effective reservoir lateral distribution modes of block concentrated development mode, medium layer and thin layer superimposed mode and Thin layer isolated model mode are proposed and their adaptability to horizontal well deployment is evaluated. The drilled reservoir is divided into three types: high-quality reservoir, suboptimal reservoir and poor reservoir, and the quantitative classification standard is established. On this basis,the decline rule and difference of horizontal well drilling in different quality reservoirs are discussed, and the quantitative evaluation standard of horizontal well development effect is established. The initial decline rates of three types of horizontal wells are 32.9%，35% and 40%, and the estimate ultimate recoveries (EUR) of three types of horizontal wells are 89 million cm3, 68 million cm3, and 31 million cm3, respectively. The results of this study provide technical support for the optimal deployment of new horizontal wells in the Sulige Gas Field and a reference for the development of horizontal wells in the same types of gas reservoirs.